PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) DAN THINK TALK WRITE (TTW) PADA MATERI EVOLUSI - Widya Ginting, Cindy; Perayanti Sinaga, Dian (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2021)
This study aims to determine the differences in student learning outcomes using the Group Investigation (GI) and Think Talk Write (TTW) learning models on the evolution material in grade XII of SMA Yayasan Perguruan Keluarga Pematangsiantar in the 2019/2020 Academic Year. The population in this study were all grade XII students of SMA Yayasan Perguruan Keluarga consisting of 3 (three) classes with a total of 103 students and the research sample was 68 students consisting of two classes, namely class XII-IA1 with 34 students as the experimental class I using the Group Investigation (GI) learning model and XII-IA2 with 34 students as the experimental class II using the Think Talk Write (TTW) learning model. Data analysis was carried out using SPSS 21 to find the average value, standard deviation and hypothesis proven using the t-test at a significance level of α = 0.05. The research results obtained an average learning outcome score of 79.26 for experimental class I using the Group Investigation (GI) learning model, and 84.12 for experimental class II using the Think Talk Write (TTW) learning model. Hypothesis testing using the t-test at a significance level of α = 0.05 and dk = 66 yielded a calculated t (3.91) > t (2.00). Therefore, H0 is rejected and Ha is accepted, indicating a difference in student learning outcomes between the Group Investigation (GI) and Think Talk Write (TTW) learning models on evolution in grade XII of SMA Yayasan Perguruan Keluarga Pematangsiantar in the 2019/2020 academic year.